Morphing technique reveals intact perception of object motion and disturbed perception of emotional expressions by low-functioning adolescents with Autism Spectrum Disorder. (December 2015) - Han, Bora; Tijus, Charles; Le Barillier, Florence; Nadel, Jacqueline
Highlights: A novel morphing design allows comparing the perception of dynamic faces and objects. Autistic visual peculiarities are limited to the perception of dynamic faces. Individuals with ASD track motion rather than emotion in expressive faces. Abstract: A morphing procedure has been designed to compare directly the perception of emotional expressions and of moving objects. Morphing tasks were presented to 12 low-functioning teenagers with Autism Spectrum Disorder (LF ASD) compared to 12 developmental age-matched typical children and a group presenting ceiling performance. In a first study, when presented with morphed stimuli of objects and emotional faces, LF ASD showed an intact perception of object change of state together with an impaired perception of emotional facial change of state. In a second study, an eye-tracker recorded visual exploration of morphed emotional stimuli displayed by a human face and a robotic set-up. Facing the morphed robotic stimuli, LF ASD displayed equal duration of fixations toward emotional regions and toward mechanical sources of motion, while the typical groups tracked the emotional regions only. Altogether the findings of the two studies suggest that individuals with ASD process motion rather than emotional signals when facing facial expressions.